STRUCTURE MODIFICATION OF ANDROGRAPHOLIDE TO IMPROVE ITS POTENCY AS ANTICANCER - Hadi Poerwono; Yoshiyuki Hattori; Hajime Kubo; Kimio Higashiyama (Universitas Gadjah Mada, 2007)
Andrographolide, a diterpenoid lactone isolated from the herb of Andrographis paniculata and known to possess antitumor activity in breast cancer models was subjected to semisynthesis leading to the preparation of a number of derivatives. After protection of the two hydroxyl groups present at C-3 and C-19 to give 3,19-isopropylidene and 3,19-benzylidene andrographolides, the remaining hydroxyl group at C-14 of andrographolide was treated with acid anhydride or acid chloride under base condition. Unfortunately, the reactions gave only 14-dehydroandrographolide as well as unidentified diacyl compounds in replace of the target molecule 14-O-acyl andrographolide. An alternative procedure using neat acetic anhydride under reflux gave the acetyl derivatives. The resulted compounds exhibited cytotoxic activity against MCF-7 breast cancer cells with better growth inhibition than the parent compound andrographolide.